2021
DOI: 10.3390/coatings11080971
|View full text |Cite
|
Sign up to set email alerts
|

A Synergistic Effect between Stearic Acid and (+)-α-Tocopherol as a Green Inhibitor on Ferritic Stainless Steel Corrosion Inhibition in 3.0% NaCl Solution

Abstract: The synergistic inhibitory effect of stearic acid and (+)-α-tocopherol (E307) as a green inhibitor within a highly hydrophobic layer on the corrosion of low-carbon ferritic stainless steels was investigated in 3.0 wt% NaCl solution at 25 °C, focusing on long-term immersion tests. For a broader characterisation of the surface properties, especially the modified surfaces, of the samples used, the following methods were chosen: SEM was used to investigate the surface morphologies, the water contact angle to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…The contact angle of a liquid droplet is a suitable means of describing the wetting properties of a surface. In our previous research, it has already been shown that hydrophobic layers formed in this way can be classified as highly hydrophobic layers, with contact angle values close to 150° (so-called superhydrophobic layers) [ 26 , 27 , 28 ]. The CA values after prolonged exposure and whether the basic structure of these layers changed after 120 h of immersion in corrosion medium (simulated acid rain) were the main objective of the contact angle measurements and taking SEM photos.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The contact angle of a liquid droplet is a suitable means of describing the wetting properties of a surface. In our previous research, it has already been shown that hydrophobic layers formed in this way can be classified as highly hydrophobic layers, with contact angle values close to 150° (so-called superhydrophobic layers) [ 26 , 27 , 28 ]. The CA values after prolonged exposure and whether the basic structure of these layers changed after 120 h of immersion in corrosion medium (simulated acid rain) were the main objective of the contact angle measurements and taking SEM photos.…”
Section: Resultsmentioning
confidence: 99%
“…The CA values after prolonged exposure and whether the basic structure of these layers changed after 120 h of immersion in corrosion medium (simulated acid rain) were the main objective of the contact angle measurements and taking SEM photos. In our previous work, the change in morphology of these coatings on the same material was observed after prolonged exposure to 3% NaCl [ 27 ]. Therefore, the surface wettability of the coatings was determined by measuring the contact angle of the water (CA), spreading 5–8 drops over the entire surface to obtain reliable CA values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations